Representasi Bad Mother Dalam Film Pengabdi Setan (Jurnal Kajian Media, 2022)
This research begins with the interest in horror films in the community and the polemic of generations with transitional periods they face. Through the movie of Pengabdi Setan, it implies conservative values covering these two things. The author aims to provide a new perspective in this. Some previous studies only provide a scientific view from the mother's side without providing a new perspective on the involvement of generations in the film.With dispositive critical discourse analysis, it can be used to analyze widely within the scope of film works, data reinforcement in this study is in the form of interviews with writers who make works with the same story pattern. The author finds the role of conservative values through the Hantu Ibu figure in providing awareness of the female womb being shaped into a Bad Mother in visual and textual terms and its relationship to the transition of the younger generation.